Ted Bell's monarch - Steck, Ryan; Bell, Ted (Bell, Ted. Alex Hawke novel, 2025)
"Following a successful but costly mission to destroy an enemy outpost in Antarctica, Alex Hawke is looking forward to some quiet time at Teakettle Cottage, his home in Bermuda, along with his family. But he's not a man who can avoid trouble. Former Chief Inspector of Scottland Yard Ambrose Congreve calls him with stunning news. Just days away from a controversial vote threatening to tear the United Kingdom apart at the seams, King Charles has disappeared while vacationing at Balmoral Castle. The prime minister believes she can keep the news quiet for no more than 72 hours. After that, Britain will be plunged into chaos. With the fate of the kingdom hanging in the balance, it's up to Lord Hawke to find and rescue the missing monarch before it's too late."--